The lost world : a novel - Crichton, Michael (New York : Alfred A. Knopf, 1995)
Six years after the events in "Jurassic Park", something has survived on a deserted Costa Rican island. A paleontologist named Richard Levine goes to the island to study it's dinosaurs. He brings with him a Costa Rican guide named Diego, two mechanics named Jack Thorne and Eddie Carr, an animal behaviorist named Sarah Harding, two stow-a-way kids named Arby and Kelly, and Dr. Ian Malcolm, who was one of the few survivors of the first dinosaur incident. However, something goes wrong once again, and the island is plunged into chaos!
Keywords: Dinosaurs -- Fiction; Cloning -- Fiction; Science fiction